Information sharing and multi-tier supply chain management of SMEs in the context of Industry 4.0 - Winter, Matthias; Dopler, Silvia; Müller, Julian M.; Zeisler, Alexander (Procedia Computer Science, 2022)
This paper investigates the transformation of information sharing and multi-tier supply chain management (MSCM) from the perspective of small and medium-sized enterprises (SMEs) in the context of Industry 4.0. SMEs are typically sharing less information digitally, are less active in conducting MSCM, but must be integrated in digital supplier networks to achieve supply chain transparency or traceability. For this purpose, this paper empirically analyzes SMEs from the manufacturing industry in Austria and Germany are investigated regarding information sharing and MSCM. The responses are analyzed to test three hypotheses, using 81 replies from manufacturing SMEs in Austria and Germany. The three hypotheses investigate the upstream and downstream MSCM practices of SMEs as well as which kind of information is shared with and by SMEs. The results help to understand and reveal potential barriers for information sharing besides technical possibilities to SMEs in order to be actively involved in MSCM.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Industry 4.0; information sharing; multi-tier; supplier networks; supply chain management